Proceedings. IEEE Lester Eastman Conference on High Performance Devices, 2004.
DOI: 10.1109/lechpd.2004.1549694
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent I-V characteristics of AlGaN/GaN HBTs and GaN BJTs

Abstract: DC I-V characteristics of AlGaN/GaN heterojunction bipolar transistors (HBTs) and GaN homojunction bipolar transistors (BJTs) are analyzed in the temperature range of 200-450 K. At low current levels, the adverse effects of poor ohmic contacts coupled with paths of high leakage make it difficult to extract intrinsic device operation ["Explanation of anomalous current gain observed in GaN based bipolar transistors", Xing et al. IEEE Elect. Dev. Lett. 24(1) 2003:p.4-6]. At intermediate current levels, owing to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…10 Here the circuit is wired in the schematic by using all the necessary components like diodes, transistors, resistors and voltage sources that are available as in-built models in the software. 11 Then the execution is done to view the output.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Here the circuit is wired in the schematic by using all the necessary components like diodes, transistors, resistors and voltage sources that are available as in-built models in the software. 11 Then the execution is done to view the output.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the main reasons for the differences are, There are fluctuations in the power supply while performing the experiment manually, but in automatic method, the DAQ supplies the power, without of any fluctuations. Effect of external noise and temperature 11 is not taken into account in the automatic method and simulation. Readings in manual method is restricted to the number of decimal points, since the range of meters available are limited. It is seen that the built in model of the BJT in the simulation software has fixed model of a transistor and the current gain (β) of the model is slightly different from the normal BJT that was used for the characterization and hence slight changes are seen in the collector current (Figure 7 ). …”
Section: A Comparative Study On the Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that heterojunction IMPATTs have some advantages over their homojunction counterparts as regards lower noise figure and reduced tunnel component of current OE12 . The heterojunction between GaN and Al x Ga 1 x N has been successfully used in high frequency semiconductor devices such as high electron mobility transistors (HEMTs) and heterojunction bipolar transistors (HBTs) OE13; 14 . This has prompted the authors to study the large-signal and noise properties of anisotype heterojunction DDR IMPATTs based on Al x Ga 1 x N/GaN material system designed to operate at 1.0 THz.…”
Section: Introductionmentioning
confidence: 99%